Multikulturalisme Dalam Video Game Dragon Age: Inquisition - Ardian Indro Yuwono; Jusuf Ariz Wahyuwono (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2016)
Abstract With the development of technology today, video games are not just simple entertainment media. Supported by the advancement of newest technology, video games able to have content, just like cinema and films. With its content, video games can not be separated from the reality that determines the content in the process of production. Including values, cultures, and ideologies that are not always visible and latent. So through this study, the authors attempted to see how the video game Dragon Age: Inquistion, popular video games Bioware under the auspices of EA Software made in America. With topics related to multiculturalism, topics that related to idea how race and cultural diversity are represented in the media. America itself into a unique country, known as a melting pot of diverse cultures in the world. But do all races and culture are equally represented in the media?Or maybe there is some stereotype to particular race and culture? So through this study, the authors attempted to see how multiculturalism represented, especially through video games.